2021
DOI: 10.3389/fsufs.2021.650987
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Sustainable Food Systems: What Should We Learn Before the Next Emergency

Abstract: Three key transitions leading to a “safe and just” operating space, with a focus on food systems, emerged during the development of a Foresight study promoted by SCAR (Standing Committee on Agricultural Research1): (a) sustainable and healthy diets for all; (b) full circularity in the use of resources; (c) diversity as a key component of stable systems. As consequence of COVID-19, food emerged again as a central element of life, along with health, after decades in which food security was taken for granted, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 54 publications
1
88
0
Order By: Relevance
“…In addition to consumers’ behavior changes, the coronavirus crisis is causing many problems and is worsening pre-existing conditions. Many people around the world have lost their jobs and inequalities related to wealth, income level and social protection have exacerbated [ 61 , 62 , 63 ]. Moreover, food insecurity [ 64 ] increased among who have already suffered from poverty in developing countries [ 65 ] but disparities came out also in developed countries [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to consumers’ behavior changes, the coronavirus crisis is causing many problems and is worsening pre-existing conditions. Many people around the world have lost their jobs and inequalities related to wealth, income level and social protection have exacerbated [ 61 , 62 , 63 ]. Moreover, food insecurity [ 64 ] increased among who have already suffered from poverty in developing countries [ 65 ] but disparities came out also in developed countries [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all currently known studies on COVID-19 in the agricultural and food sector discuss the adverse effects of COVID-19. However, some scholars have also reported a significant increase in online sales channels of agri-food under COVID-19 [65,66]. We believe that expanding online sales may minimize the impact of COVID-19.…”
Section: Discussionmentioning
confidence: 80%
“…The poorest groups are most threatened under the impact of the pandemic. Bisoffi et al [65] observed the weakness of the global governance mechanism under the pandemic, Ecological agriculture and food processing industries may be affected by the economic recession caused by the pandemic. Taken together, the pandemic affects agriculture and food in many ways, including but not limited to the following [65]:…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts are consistent with SDG 11, which calls for cities to be inclusive, safe, resilient, and sustainable. Diversification of urban farms is the primary strategy for achieving a sustainable agricultural system in both the biophysical and social spheres [35]. According to Alterie and Nicholls [29], self-sufficiency in vegetables can be achieved at the community or city level if urban farms are redesigned based on an agroecological management.…”
Section: The Rise Of Urban Agroecologymentioning
confidence: 99%
“…Economic slowdowns have been observed in the pandemic's initial epicenters, including China, Europe, and the United States, which have spread to middle-and low-income countries for a variety of reasons, including declines in trade and commodity prices [39]. Under these conditions, it justifies why urban agriculture has emerged as a critical means of addressing local food and nutrition insecurity, particularly through agroecological approaches that benefit smallholder farming systems located in cities, megacities, or megapolises [35,40].…”
Section: "En Route" To Achieving Resilient Cities Through Agroecological Practicesmentioning
confidence: 99%